The feminist standpoint theory reader: Intellectual and political controversies - Harding, Sandra G. (Routledge, 2004)
Leading feminist scholar and one of the founders of Standpoint Theory, Sandra Harding brings together the biggest names in the field–Dorothy Smith, Donna Haraway, Patricia Hill Collins, Nancy Hartsock and Hilary Rose–to not only showcase the most influential essays on the topic but to also highlight subsequent interrogations and developments of these approaches from a wide variety of disciplines and intellectual and political positions.
https://books.google.ca/books?id=qmSySHvIy5IC&printsec=frontcover&hl=fr&source=gbs_ViewAPI&redir_esc=y#v=onepage&q&f=false
Keywords: approches et analyses; cours; discipline; fem1000; har4600; incontournable; interdisciplinarité; point de vue situé; pol4212; premier cycle; privilèges; ressource en ligne; sciences humaines; systèmes d'oppressions; épistémologie

Le contrat social entre frères - Pateman, Carole (Repenser le politique : l'apport du féminisme, 2004)
https://books.openedition.org/bibpompidou/1427?lang=fr#text Première publication: 1988
Keywords: amériques; citoyenneté; cours; discipline; fem1000; histoire et politique; incontournable; premier cycle; régions géographiques; science politique; science politique et droit; thématiques; théories féministes; états-unis